The Effect of Smartphone and Vehicle Distance on Vehicle Safety System Time Response Based on the Internet of Things - Arkan, Ghazy; Martawati, Mira Esculenta (Universitas Semarang, 2023)
This paper addresses the prevalent issue of increasing crimes in Indonesia, particularly vehicle thefts. To combat this challenge, we propose the development of an Internet of Things (IoT)-based vehicle security device capable of detecting intruders within the car and subsequently notifying the car owner through smartphone alerts. The implementation of this innovative technology holds the potential to enhance vehicle security and contribute to a safer environment for vehicle owners in the country. In this study, we conducted a series of tests in a rural mountain area to examine the impact of vehicle and smartphone distance variation, as well as internet provider variation, on the response time of a vehicle safety device under limited internet signal conditions. The experiment involved distance variations of 100m, 200m, 300m, 400m, 500m, and 600m, with the internet providers being the most expensive and the cheapest provider in Indonesia. By investigating these factors, we aimed to gain insights into optimizing the response time of the safety device, especially in areas with poor internet connectivity. Utilizing the two-way ANOVA method, this experiment successfully demonstrates that variations in distances and internet providers significantly influence the notification response. The effective combination of the HC-SR501 passive infrared sensor and Nodemcu microcontroller is shown to detect movements inside the vehicle cabin and reliably notify the vehicle owner through their smartphone. These findings underscore the viability and efficiency of the proposed system in enhancing vehicle security and owner awareness.